The effects of removable vs fixed twin block appliances on the oral and gingival health. A randomized clinical trial - Y. Mostafa, Omar; Magdi, Sally; El Sharaby, Fouad A.; El Dawlatly, Mostafa M (Journal of Neonatal Surgery, 2025)
Introduction: Twin block appliance (TB) has been used for decades as a gold standard treatment for class 2 skeletal malocclusion in growing patients. Different designs of fixed twin block appliances have been introduced recently. The aim of this study is to investigate the oral side effects associated with fixed or removable twin block appliance. methodology: a group of 24 skeletal class 2 patients with deficient mandible were randomly received either fixed twin block or removable twin block appliance and followed up for 9 months to investigate the oral and gingival effects. The results: showed that speech and eating difficulties was evident in the fixed twin block group for only one week. Redness of palatal mucosa was evident in some cases of the removable appliance but without pain or signs of candida infection. This was healed after appliance discontinuation. The oral hygiene was the main factor influencing the oral and gingival health. The cephalometric measurements showed significant proclination of the lower incisors in both groups with insignificant decrease in the thickness of the labial bone. Conclusion: both fixed and removable appliance cause lower incisor proclination but with no significant decrease in the labial alveolar bone thickness, the gingival health is mainly affected by the oral hygiene not the type of the appliance, The gingival and mucosal redness, swelling, speech or eating difficulties associated with twin block was temporary and not significant.